2012
DOI: 10.1111/j.1528-1167.2012.03724.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP differentially affects epileptiform activity via purinergic P2X7 and adenosine A1 receptors in naive and chronic epileptic rats

Abstract: SUMMARYPurpose: Adenosine is considered an endogenous anticonvulsant. However, much less is known about the putative effects of its precursor, ATP, on epilepsy. Therefore, we tested whether ATP and its receptors are able to modulate epileptiform activity in the medial entorhinal cortex of the rat. Methods: Recurrent epileptiform discharges (REDs) were induced by elevating extracellular potassium concentration combined with application of bicuculline in brain slices from naive and pilocarpine-treated chronic ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…This minor role was echoed by ATP biosensor measurements, which showed little appreciable release of ATP during either evoked seizure activity or spontaneous seizures caused by the elevation of extracellular K + to 6 mM, both of which were capable of provoking considerable adenosine release (Figure 6). Thus, under these conditions there seems to be both little ATP release and little P2 receptor involvement in modulating epileptiform activity, observations confirmed by others (Klaft et al, 2012). However, these findings do not preclude the potential importance of ATP release and P2 receptors in other seizure models or conditions (Burnstock et al, 2011).…”
Section: Insight Into the Regulation Of Basal And Seizure-induced Pursupporting
confidence: 71%
“…This minor role was echoed by ATP biosensor measurements, which showed little appreciable release of ATP during either evoked seizure activity or spontaneous seizures caused by the elevation of extracellular K + to 6 mM, both of which were capable of provoking considerable adenosine release (Figure 6). Thus, under these conditions there seems to be both little ATP release and little P2 receptor involvement in modulating epileptiform activity, observations confirmed by others (Klaft et al, 2012). However, these findings do not preclude the potential importance of ATP release and P2 receptors in other seizure models or conditions (Burnstock et al, 2011).…”
Section: Insight Into the Regulation Of Basal And Seizure-induced Pursupporting
confidence: 71%
“…P2X7R have been shown to modulate mechanisms involved with apoptosis/necrosis and neuronal differentiation of NPCs [87][88][89][90], while P2Y1 receptors modulate proliferation and migration of NPCs [91][92][93]. Klaft et al [94] also found that P2X7R antagonists had a minor antiepileptic effect in medial entorhinal cortex on rats subjected to pilocarpine-induced epilepsy.…”
Section: Discussionmentioning
confidence: 88%
“…It has also been demonstrated in the hippocampus that glutamate increases the Ado level via NMDA receptor activation, which may inhibit glutamate release presynaptically via A 1 receptors [102]. The inhibition by Ado may be sufficient (i) to regulate the spreading of seizures, (ii) to decrease epileptic activity ( Table 3) and (iii) for seizure termination [96,101,[103][104][105][106][107][108]. An increase in the Ado level in epileptic brain tissue has been demonstrated [109][110][111][112].…”
Section: Adenosinementioning
confidence: 99%